(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
As society faced issues with the widespread dissemination of disinformation, this study aimed to investigate the ESSU-Maydolong students’ knowledge, extent of practice, and challenges of information and media literacy. This descriptive correlational study utilized the weighted mean, chi-square test, and Spearman rho to describe data and determine the association of variables. Findings reveal that ESSU-Maydolong students were knowledgeable about information literacy and highly knowledgeable relating to their practical understanding of media literacy. However, the students often practiced their IML skills and agreed that they perceived challenges concerning IML skill utilization. The study also determined a significant relationship between the following: (1) respondents’ demographic characteristics (sex and sex) and their knowledge of information and media literacy; (2) respondents’ knowledge of IML and the extent of the practice of their skills in IML; as well as their challenges in the respondents’ basic understanding of information and media literacy.